Non-coding RNAs as regulators of the Hippo pathway in cardiac development and cardiovascular disease - Song, Mengyang; Wang, He; Liu, Caixia; Jin, Sijie; Liu, Bin; Sun, Wei (Frontiers in Pharmacology, 2024)
Cardiovascular diseases pose a serious threat to human health. The onset of cardiovascular diseases involves the comprehensive effects of multiple genes and environmental factors, and multiple signaling pathways are involved in regulating the occurrence and development of cardiovascular diseases. The Hippo pathway is a highly conserved signaling pathway involved in the regulation of cell proliferation, apoptosis, and differentiation. Recently, it has been widely studied in the fields of cardiovascular disease, cancer, and cell regeneration. Non-coding RNA (ncRNAs), which are important small molecules for the regulation of gene expression in cells, can directly target genes and have diverse regulatory functions. Recent studies have found that ncRNAs interact with Hippo pathway components to regulate myocardial fibrosis, cardiomyocyte proliferation, apoptosis, and hypertrophy and play an important role in cardiovascular disease. In this review, we describe the mode of action of ncRNAs in regulating the Hippo pathway, provide new ideas for further research, and identify molecules involved in the mechanism of action of ncRNAs and the Hippo pathway as potential therapeutic targets, with the aim of finding new modes of action for the treatment and prevention of cardiovascular diseases.